Eastern Ideas on Governance: Can it Inform Nepali Policy Makers? - Dahal, Dev Raj (NCWA Annual Journal, 2026)
This article explores how Eastern philosophical traditions and worldviews can inform and enhance governance practices in Nepal. It emphasizes the multifaceted nature of human existence—biological, societal, and cosmological—and advocates for a holistic approach rooted in Eastern thought, including Hinduism, Buddhism, Confucianism, and other indigenous philosophies. The piece contrasts the East's systemic, interdependent worldview with the West's binary, conflict-oriented paradigm, highlighting the importance of cosmic harmony, moral virtues, and the golden mean in governance. It underscores the role of knowledge, wisdom, and culture in shaping just, sustainable, and participatory governance at multiple levels. The article also discusses the significance of philosophers as advisors, the need for contextualized policies, and the importance of integrating indigenous values with modern governance frameworks. Ultimately, suggested that embracing Eastern philosophical insights can help Nepali policymakers foster justice, social cohesion, and resilience amid structural and political challenges, paving the way for a more equitable and sustainable future.